2016
DOI: 10.1159/000444810
|View full text |Cite
|
Sign up to set email alerts
|

MLC901 Favors Angiogenesis and Associated Recovery after Ischemic Stroke in Mice

Abstract: Background: There is increasing evidence that angiogenesis, through new blood vessel formation, results in improved collateral circulation and may impact the long-term recovery of patients. In this study, we first investigated the preventive action of a 5-week pretreatment of MLC901, an herbal extract preparation derived from Chinese medicine, against the deleterious effects of ischemic stroke and its effects on angiogenesis in a model of focal ischemia in mice. Methods: The stroke model was induced by 60 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 60 publications
(94 reference statements)
6
37
0
5
Order By: Relevance
“…MLC901, an herbal extract preparation modified from the TCM herbal formula, has been proven to have neuroprotective and neurorestorative properties in preclinical models of stroke, traumatic brain injury, and global cerebral ischemia. Gandin et al (2016) found that 5-week pretreatment with MLC901 in MCAOinduced cerebral ischemia mouse models could regulate the expression of HIF-1α and its downstream targets, such as VEGF, Ang-1, and Ang-2. Chen et al showed that administration of TCM formula Bu Yang Huan Wu (BYHW) decoction decreased cerebral edema, the neurological deficient score, and brain infarct volume in a rat model of cerebral ischemia/reperfusion (I/R) injury.…”
Section: Activators Of Hif-1 Mrna And/or Protein Expressionmentioning
confidence: 95%
See 1 more Smart Citation
“…MLC901, an herbal extract preparation modified from the TCM herbal formula, has been proven to have neuroprotective and neurorestorative properties in preclinical models of stroke, traumatic brain injury, and global cerebral ischemia. Gandin et al (2016) found that 5-week pretreatment with MLC901 in MCAOinduced cerebral ischemia mouse models could regulate the expression of HIF-1α and its downstream targets, such as VEGF, Ang-1, and Ang-2. Chen et al showed that administration of TCM formula Bu Yang Huan Wu (BYHW) decoction decreased cerebral edema, the neurological deficient score, and brain infarct volume in a rat model of cerebral ischemia/reperfusion (I/R) injury.…”
Section: Activators Of Hif-1 Mrna And/or Protein Expressionmentioning
confidence: 95%
“…Chinese herbal medicines often use a variety of herbs in different complex combinations to enhance their therapeutic effects or reduce their toxicity. Growing evidence has demonstrated potential proangiogenic benefits of Chinese herbal medicines in ischemic stroke whereas tumor angiogenesis could be inhibited by the active components in herbal medicines (Hong et al, 2015;Gandin et al, 2016;Hong et al, 2016;Guo et al, 2018). Thus, the objective of this review is to provide comprehensive insight on how Chinese herbal medicines impact angiogenesis by regulating HIF-1 pathways in both cancer and ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…A critical molecular pathway induced by hypoxia/ischemia is the activation of hypoxiainducible factor 1, a transcriptional activator of genes encoding VEGF and other important mediators of angiogenesis. Hif1 is the central transcriptional factor for the regulation of oxygen-associated genes in response to hypoxia (Gandin et al 2016). In the key restorative mechanisms in response to stroke, there is increasing evidences that angiogenesis, through new blood vessel formation, results in improved collateral circulation and may impact the long-term recovery of the patients (Gandin et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These beneficial effects have also been observed in an in vitro assay of oxygen-glucose deprivation that mimics brain ischemic conditions 25 . Both MLC601 and MLC901 are cocktail of molecules acting on many different targets such as free radical production (inhibition), ATP-sensitive K + channels (activation) 15 , 16 , 25 or HIF1α (Hypoxia-Inducible Factor 1-alpha), EPO (erythropoietin), VEGF (Vascular Endothelial Growth Factor) expression 26 .…”
Section: Introductionmentioning
confidence: 99%